The Limited Positive Publication System in the Land Sector, Solution Towards Legal Certainty and Fair Legal Protection - Suharyono Suharyono; Muhamad Sadi Is; Sobandi Sobandi (JURNAL AKTA, 2024)
Land registration using the negative publication system had positive elements used in Government Regulation Number 24 of 1997 was believed to create just legal certainty. This research used a normative juridical approach, and supported by primary, secondary and tertiary data. The research results showed that certificates which were the products of the National Land Agency/Land Office had not been able to realize legal certainty that was fair to rights holders. This was reinforced by a number of court decisions canceling land certificates. The results of these findings recommended that a positive (limited) publication system was used as an alternative solution to realize legal certainty that was fair to people applying for land registration applications.